2016
DOI: 10.3892/or.2016.5234
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 is involved in resistance to 5-FU in colon cancer cells

Abstract: Resistance to 5-fluorouracil (5‑FU), a key drug in the treatment of colorectal cancer, is one of the major reasons for poor patient prognosis during cancer treatment. Annexin A1 (ANXA1) is a calcium‑dependent phospholipid‑linked protein that is associated with drug resistance, anti‑inflammatory effects, regulation of cellular differentiation, proliferation and apoptosis. Although there have been several studies investigating ANXA1 expression in drug resistant cells, the role of ANXA1 is yet to be fully underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 24 publications
2
61
0
Order By: Relevance
“…Jia et al found that knocking down ANXA1 enhanced the chemosensitivity of multiple myeloma cells to bortezomib (40). Onozawa et al found that overexpression of ANXA1 is associated with increased 5-FU resistance in colon cancer cells (41). Wang et al detected increased expression of ANXA1 mRNA and protein in cisplatin-resistant lung cancer A549 cells and lung adenocarcinoma tissues (42).…”
Section: Discussionmentioning
confidence: 99%
“…Jia et al found that knocking down ANXA1 enhanced the chemosensitivity of multiple myeloma cells to bortezomib (40). Onozawa et al found that overexpression of ANXA1 is associated with increased 5-FU resistance in colon cancer cells (41). Wang et al detected increased expression of ANXA1 mRNA and protein in cisplatin-resistant lung cancer A549 cells and lung adenocarcinoma tissues (42).…”
Section: Discussionmentioning
confidence: 99%
“…We found 56 common differentially expressed proteins between the chemoresistant and the corresponding parent cell lines. Some proteins, such as HSPB1, 36,37 and ANXA1 38,39 have been reported on NPC or other cancers, whereas some proteins, such as PRDX1, STMN1, and TALDO1 were discovered in our study. Using iTRAQ labeling combined with NanoLC-MS/MS, we identified a spectrum of CDDP resistance-associated proteins in NPC cell lines that provides insights into the resistance mechanism of cancer cells.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, the differential expression of ANXA1 and TRIM29 were confirmed further with PCR and western blotting, because our previous study showed that overexpression of this protein could promote invasion and metastasis of NPC. 39,67 The tripartite motif (TRIM) family characterized by a series of conserved domains, including a Ring-finger domain, one or two B-box zinc-finger motifs, and a coiledcoil domain, comprises multi-domain ubiquitin E3 ligases. Thus far, some of the TRIM family proteins are reported to regulate important cellular processes such as cell proliferation, migration, invasion, and carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The colon cancer cases with positive ANXA1 staining were not statistically associated with poor survival 5) . However, our recent findings suggested that upregulated ANXA1 expression may play a critical role in 5-FU resistance in colon cancer cells, indicating the association between ANXA1 and worsened colon cancer outcome 6) . In gastric cancer, ANXA1 is also thought to play a critical role in cancer development 7,8) .…”
Section: Introductionmentioning
confidence: 86%
“…IHC staining was performed as previously described 6,11) . Briefly, gastric cancer cells were fixed in 10% formalin and embedded in paraffin, then cut into 4 μm sections and stained.…”
Section: Ihc Staining and Evaluationmentioning
confidence: 99%